Problem Based Learning Model with Culturally Responsive Teaching Approach to Cultural Literacy and Social Interaction of Grade IV Elementary School Students - I Gusti Bagus Made Bramanta Daniswara; I Gede Astawan; Gusti Ayu Putu Sukma Trisna (Jurnal Pendidikan Multikultural Indonesia, 2025)
Students' knowledge and interest in local culture are still low due to the increasingly rapid flow of globalization. Students also feel uncomfortable and have difficulty adapting to social norms that apply in schools because of differences in values, habits, and ways of communicating. This study aims to investigate the effect of the Problem Based Learning learning model with the Culturally Responsive Teaching approach on cultural literacy and social interaction of fourth grade elementary school students. The type of research is quasi-experimental with a Nonequivalent Pre-Test Post Test Control Group Design. The population in the study were all fourth grade students of Elementary School Gugus VII, Tabanan District. The research sample was taken using a random sampling technique with a randomized class as an intact group with 21 people as the experimental group and 19 people as the control group. The data collection method uses a non-test method with a questionnaire instrument. The analysis method uses descriptive statistics and inferential statistics (t-test and Manova test). Based on the results of the t-test, the significant value of cultural literacy and social interaction is 0.000 <0.05. Then from the results of the Manova test, the significance value is 0.000 <0.05 so that it can be concluded simultaneously that there is a significant influence of the PBL learning model with the CRT approach on cultural literacy and social interaction of fourth grade elementary school students. The implications of this study are that it can improve cultural literacy and social interaction of students, and can be a reference for teachers and schools in designing more relevant and meaningful learning for students.